Heat-conducting wave-absorbing electromagnetic functional material and preparation method thereof

By depositing boron nitride/PVDF nanofibers on carbon fiber fabrics and combining high-temperature pyrolysis treatment and vacuum impregnation technology, thermal wave absorption electromagnetic material with strong attenuation characteristics, high thermal conductivity and high strength was prepared, and the existing materials were solved. The problem of performance degradation when increasing the content of a certain functional filler meets the demand for high-performance electromagnetic materials of multifunctional electronic devices.

CN119463416APending Publication Date: 2025-02-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411394459.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing thermally conductive and wave-absorbing electromagnetic composite materials increase the content of a certain functional filler, it is easy to lead to the decline or loss of another performance, which is difficult to meet the demand for high-performance electromagnetic materials of multifunctional electronic devices.

Method used

Electrospinning method is used to deposit boron nitride/PVDF nanofibers on the carbon fiber fabric layer, and carbon fiber/boron nitride micro-nano fiber mats are formed by high-temperature pyrolysis treatment, and carbonyl iron powder is mixed with epoxy resin to form a magnetic slurry. The slurry is soaked into the fibrous structure by vacuum impregnation, cured and molded, and a thermal wave-absorbing electromagnetic functional material is prepared.

Benefits of technology

实现了材料的强衰减特性、高导热、高强度可加工等特点,能够满足多类电子设备及器件对高性能电磁材料的应用要求,显著提升了材料在宽频带范围的电磁波衰减性能和机械强度 .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073367320000051
    Figure BDA0005073367320000051
Patent Text Reader

Abstract

The invention discloses a heat-conducting wave-absorbing electromagnetic functional material and a preparation method thereof, and belongs to the technical field of electromagnetic materials. The preparation method comprises the following steps: introducing boron nitride nanosheets into a carbon fiber fabric structure by adopting an electrostatic spinning and high-temperature pyrolysis technology to form a continuous heat-conducting and electricity-conducting network structure, and impregnating carbonyl iron powder / epoxy resin electromagnetic slurry containing magnetic loss into a composite material through vacuum-assisted perfusion to prepare the heat-conducting and wave-absorbing electromagnetic functional material. The problems that a traditional heat conduction network structure is poor in continuity and weak in broadband attenuation capacity are solved, and the heat conduction effect and the electromagnetic broadband attenuation performance of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic materials, and specifically relates to a heat-conducting and wave-absorbing electromagnetic functional material and a preparation method thereof. Background Art

[0002] As high-performance radio frequency systems develop towards high-power, multi-functional integration, electromagnetic materials with electromagnetic wave absorption and heat transmission functions will be widely used in equipment and devices to eliminate internal clutter, and at the same time, the heat generated between devices will be timely conducted and dissipated, so as to achieve stable operation of the entire electronic system. Due to the necessary factors such as limited internal space of the equipment, variable frequency bands, and high-power transmission and reception, the comprehensive performance requirements for such materials have become more and more, and the more typical ones are broadband strong attenuation ability, low density and light weight, high-strength load-bearing, easy conformal processing, etc. Therefore, an electromagnetic material with excellent thermal conductivity and wave absorption function is developed to solve the bottleneck problem with foreseeable future. The present invention is to develop an electromagnetic functional composite material with double efficiency loss, high thermal conductivity and high strength.

[0003] At present, thermally conductive and electromagnetically absorbing composite materials are mainly made by adding various types, different morphologies, and different sizes of absorbers and thermally conductive fillers to the polymer matrix, and adjusting the content ratio of the functional powder to obtain dual-functional effects. However, since these types of fillers vary in size and are arranged randomly, the compatibility effects in the matrix vary greatly, resulting in an upper limit on the total amount of multifunctional composite fillers added. Simply increasing the content of a certain functional filler will inevitably lead to a decrease or loss of another performance. For example, too much thermally conductive filler will cause a significant decrease in the electromagnetic wave absorption effect, affecting the actual application effect of the final product in electronic equipment.

[0004] Carbon fiber is a resistive absorbing functional material with excellent dielectric properties. Its large dielectric constant makes it easy to reflect electromagnetic waves when used alone as an absorber, but it lacks loss of electromagnetic waves, resulting in disadvantages such as low absorption intensity and narrow frequency band. Boron nitride, as an insulating thermal conductive material, not only has a high thermal conductivity, but also has excellent electrical insulation and a low dielectric constant. It is a good choice for adjusting the impedance matching characteristics of absorbing materials. Carbonyl iron powder is one of the absorbers with better magnetic characteristics at present, which helps to adjust the absorption bandwidth and absorption intensity, but its density is relatively high. Adding too much is not conducive to reducing the weight of the overall absorbing material.

[0005] The present invention deposits boron nitride / PVDF nanofibers on a carbon fiber fabric layer by electrospinning, accumulates carbon fiber / boron nitride / PVDF micro-nano fibrous structures layer by layer in sequence, and then forms carbon fiber / boron nitride micro-nano fiber felt by high-temperature pyrolysis treatment, further mixes epoxy resin with carbonyl iron powder to form a magnetic slurry, and uses vacuum impregnation to infiltrate the slurry into the carbon fiber / boron nitride micro-nano fiber felt, and then solidifies and forms, thereby preparing a thermally conductive and wave-absorbing electromagnetic functional material, which has the characteristics of strong attenuation characteristics, high thermal conductivity, high strength and machinability, and can meet the application requirements of various types of electronic equipment and devices for high-performance electromagnetic materials. Summary of the invention

[0006] The purpose of the present invention is to overlap boron nitride nanosheets with carbon fiber fabrics through electrostatic spinning and high-temperature pyrolysis to form a continuous thermal and electrical conductive network structure, and then impregnate and composite carbonyl iron powder with magnetic loss characteristics, so as to provide an electromagnetic functional composite material with strong attenuation characteristics, high thermal conductivity and high strength through the functional integration of multiple materials.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a heat-conducting and wave-absorbing electromagnetic functional material comprises the following steps:

[0009] 1) DMSO (dimethyl sulfoxide), DMF (N,N-dimethylformamide) and acetone are mixed evenly, and then BNNS powder (boron nitride nanosheets) is added and subjected to ultrasonic stirring to obtain BNNS slurry;

[0010] 2) mixing the BNNS slurry with cellulose nanofibers and PVDF powder (polyvinylidene fluoride), and subjecting the mixture to ultrasonic stirring to obtain a composite spinning solution;

[0011] 3) adding the composite spinning solution into a syringe and installing it in a micro-metering pump to continuously deposit BNNS / PVDF nanofibers on a carbon fiber fabric substrate to obtain a single-layer BNNS / PVDF / carbon fiber composite felt;

[0012] 4) The surface of the single-layer BNNS / PVDF / carbon fiber composite felt is then covered with carbon fiber fabric, and BNNS / PVDF nanofibers are spun and deposited, and a multilayer BNNS / PVDF / carbon fiber composite felt is obtained after repeated several times;

[0013] 5) heat treating the multilayer BNNS / PVDF / carbon fiber composite felt to obtain a BNNS / carbon fiber composite felt;

[0014] 6) Weigh spherical carbonyl iron powder, epoxy resin, propylene oxide butyl ether, and 2-ethyl-4-methylimidazole, stir evenly, and obtain carbonyl iron powder / epoxy resin electromagnetic slurry after vacuum degassing;

[0015] 7) Slowly pour the carbonyl iron powder / epoxy resin electromagnetic slurry onto the surface of the BNNS / carbon fiber composite felt, repeatedly vacuumize to make the slurry completely infiltrate into the fibrous structure, and solidify and shape to obtain a thermal conductive and wave absorbing electromagnetic functional material.

[0016] Furthermore, in step 1), the volume ratio of DMSO, DMF and acetone is (10-15):(10-20):(5-10); if the volumes of DMSO, DMF and acetone are 10-15 mL, 10-20 mL and 5-10 mL respectively, the mass of the added BNNS powder is 0.5-1.2 g, and the BNNS powder is weighed according to the current volume-mass relationship.

[0017] Furthermore, the specifications of the BNNS powder in step 1) are: particle size 0.8-3 μm, and flake diameter ratio 50-80.

[0018] Furthermore, in step 1), ultrasonic stirring is performed for 20-30 min.

[0019] Furthermore, in step 2), the mass ratio of cellulose nanofibers to PVDF powder is (0.05-0.1):(5-12), the content of cellulose nanofibers is 0.15%-0.17%, and the content of PVDF powder is 16%-20%.

[0020] Furthermore, in step 2), ultrasonic stirring is performed for 1-1.5 h.

[0021] Furthermore, in step 3), 20-35 mL of the composite spinning solution is weighed and added to the syringe, and the continuous deposition conditions on the carbon fiber fabric substrate are: voltage 12-15 kV, propulsion rate 0.5-1.5 mL / h, spinning distance 10-14 cm, receiving roller speed 250-400 r / min, spinning temperature 20-25°C, humidity 40%-60%, and single spinning time 45-60 min.

[0022] Furthermore, the spinning deposition conditions in step 4) are: voltage 12-15 kV, propulsion rate 0.5-1.5 mL / h, spinning distance 10-14 cm, receiving roller speed 250-400 r / min, and repeated deposition 10-15 times.

[0023] Furthermore, in steps 3) and 4), the thickness of the carbon fiber fabric is 0.15 mm, and the diameter of the single fiber is 5-8 μm.

[0024] Furthermore, in step 5), the heat treatment conditions are: treatment at 650-800° C. for 20-40 min; and the heat treatment atmosphere is a nitrogen or argon atmosphere.

[0025] Furthermore, in step 6), the mass ratio of spherical carbonyl iron powder, epoxy resin, propylene oxide butyl ether, and 2-ethyl-4-methylimidazole is (30-55):(35-55):(7-10):(3-5).

[0026] Furthermore, in step 6), the particle size of the spherical carbonyl iron powder is 2-3 μm, and the viscosity of the epoxy resin is 2000-2500 cps.

[0027] Further, in step 6), stirring is performed for 30-40 minutes.

[0028] Furthermore, in step 7), the vacuuming is repeated 6-10 times, and the vacuum-assisted single time lasts 20-35 seconds; the curing molding conditions are: first curing at 80° C. for 1 hour, and then curing at 100° C. for 4 hours.

[0029] A heat-conducting and wave-absorbing electromagnetic functional material is prepared by the above-mentioned preparation method.

[0030] The innovative features of the present invention are as follows:

[0031] (1) The present invention uses electrospinning to deposit BNNS / PVDF nanofibers in the gap structure of carbon fiber fabrics, further enriching the nanoscale structure in the fibrous network, which helps to form a continuous heat-conducting interconnected network structure, thereby improving thermal conductivity. At the same time, the introduction of BNNS helps to adjust the electromagnetic wave matching characteristics of the composite structure.

[0032] (2) The present invention uses high-temperature pyrolysis to crack and carbonize the organic phase PVDF in the BNNS / PVDF / carbon fiber composite felt, which not only effectively combines BNNS with carbon fiber, but also further improves the microstructure in the heat conduction network link, which helps to improve the thermal conductivity.

[0033] (3) The present invention uses a vacuum-assisted method to inject a liquid matrix with magnetic loss function into a composite fiber structure, thereby achieving diversification of the material's electromagnetic loss characteristics (resistance loss and magnetic loss), thereby improving the material's broadband electromagnetic wave attenuation performance.

[0034] The present invention has achieved the following beneficial effects:

[0035] (1) In order to solve the problems of poor network structure continuity and low thermal conductivity in traditional mechanical blending methods, the present invention introduces BNNS with electromagnetic wave tuning and thermal conductivity into the carbon fiber fabric structure through electrospinning, fills the void structure in the fiber network structure, improves the interconnected structure of the thermal conductive network, and can achieve a significant improvement in the thermal conductivity effect.

[0036] (2) The present invention is based on the principle of multi-scale complementary construction in the wave absorbing / heat conducting network structure. Nano-scale carbon fiber, BNNS and micron-scale carbon fiber fabric are effectively combined by high-temperature carbonization, which can not only effectively improve the electromagnetic matching and attenuation characteristics, but also enrich the structural scale of the thermal conductive network.

[0037] (3) The present invention aims to solve the problem of single loss mechanism and weak broadband attenuation by introducing magnetic carbonyl iron powder and injecting electromagnetic slurry into the fibrous structure by vacuum-assisted infusion, so that the material has a polymorphic structure and an electromagnetic functional phase with dual loss mechanisms, thereby effectively improving the electromagnetic attenuation ability of the material in a broadband range. DETAILED DESCRIPTION

[0038] In order to make the various technical features and advantages or technical effects of the above technical solution of the present invention more obvious and easy to understand, the following is a detailed description through examples. The epoxy resin used in the examples is bisphenol A type epoxy resin, and its complex dielectric constant is 3.2-0.12j and its complex magnetic permeability is 1.1-0.01j.

[0039] Example 1

[0040] 10 mL DMSO, 10 mL DMF, and 5 mL acetone were weighed and mixed by magnetic stirring, and then 0.5 g BNNS powder was poured in, ultrasonically dispersed and stirred for 20 min; then 0.05 g cellulose nanofibers and 5 g PVDF powder were added, ultrasonically dispersed and stirred for 1 h; further, 20 mL spinning solution was weighed, and BNNS / PVDF nanofibers were deposited on the carbon fiber fabric under the conditions of voltage 12 kV, propulsion rate 0.5 mL / h, spinning distance 10 cm, receiving roller speed 250 r / min, temperature 20 ° C, and humidity 60% to form a single-layer BNNS / PVDF / carbon fiber composite felt; the deposition was further repeated 10 times, each time for 60 min, to form 10 layers of BNNS / PVDF / carbon fiber composite felt; the composite felt was treated in a nitrogen atmosphere at 650 ° C for 20 min;

[0041] Weigh 30g of spherical carbonyl iron powder, 55g of epoxy resin, 10g of propylene oxide butyl ether, and 5g of 2-ethyl-4-methylimidazole, mix and stir for 30 minutes to form a gray electromagnetic slurry; pour the slurry onto the surface of the heat-treated fiber composite felt, repeatedly vacuum-assisted for 6 times at room temperature (20 seconds each time) to allow the slurry to completely penetrate into the fibrous structure of the composite felt, and cure and shape at 80℃ / 1h and 100℃ / 4h to obtain a thermally conductive and wave-absorbing electromagnetic functional material.

[0042] Example 2

[0043] 15 mL DMSO, 20 mL DMF, and 10 mL acetone were weighed and mixed by magnetic stirring, and then 1.2 g BNNS powder was poured in, ultrasonically dispersed and stirred for 30 min; then 0.1 g cellulose nanofibers and 12 g PVDF powder were added, ultrasonically dispersed and stirred for 1.5 h; further, 35 mL spinning solution was weighed, and BNNS / PVDF nanofibers were deposited on carbon fiber fabric under the conditions of voltage 15 kV, propulsion rate 1.5 mL / h, spinning distance 14 cm, receiving roller speed 400 r / min, temperature 25 ° C, and humidity 40% to form a single layer of BNNS / PVDF / carbon fiber composite felt; the deposition was further repeated 15 times, each time for 45 min, to form 15 layers of BNNS / PVDF / carbon fiber composite felt; the composite felt was treated in an argon atmosphere at 800 ° C for 40 min;

[0044] Weigh 55g of spherical carbonyl iron powder, 35g of epoxy resin, 7g of propylene oxide butyl ether, and 3g of 2-ethyl-4-methylimidazole, mix and stir for 40min to form a gray electromagnetic slurry; pour the slurry onto the surface of the heat-treated fiber composite felt, repeatedly vacuum-assisted 10 times at room temperature (35 seconds each time) to allow the slurry to completely penetrate into the fibrous structure of the composite felt, and cure and shape at 80℃ / 1h and 100℃ / 4h to obtain a thermally conductive and absorbing electromagnetic functional material.

[0045] Example 3

[0046] 12 mL DMSO, 15 mL DMF, and 8 mL acetone were weighed and mixed by magnetic stirring, and then 1.0 g BNNS powder was poured in, ultrasonically dispersed and stirred for 25 min; then 0.08 g cellulose nanofibers and 10 g PVDF powder were added, ultrasonically dispersed and stirred for 1.3 h; further, 30 mL spinning solution was weighed, and BNNS / PVDF nanofibers were deposited on carbon fiber fabric under the conditions of voltage 14 kV, propulsion rate 1.25 mL / h, spinning distance 13 cm, receiving roller speed 320 r / min, temperature 23 ° C, and humidity 55% to form a single-layer BNNS / PVDF / carbon fiber composite felt; the deposition was further repeated 14 times, each time for 55 min, to form 14 layers of BNNS / PVDF / carbon fiber composite felt; the composite felt was treated in a nitrogen atmosphere at 720 ° C for 30 min;

[0047] Weigh 50g of spherical carbonyl iron powder, 38g of epoxy resin, 7.7g of propylene oxide butyl ether, and 4.3g of 2-ethyl-4-methylimidazole, mix and stir for 35min to form a gray electromagnetic slurry; pour the slurry onto the surface of the heat-treated fiber composite felt, repeatedly vacuum-assisted 8 times at room temperature (30 seconds each time) to allow the slurry to completely penetrate into the fibrous structure of the composite felt, and cure and shape at 80℃ / 1h and 100℃ / 4h to obtain a thermally conductive and wave-absorbing electromagnetic functional material.

[0048] Comparative Example 1 (Compared with Example 1)

[0049] Weigh 30 g of spherical carbonyl iron powder, 55 g of epoxy resin, 10 g of propylene oxide butyl ether, and 5 g of 2-ethyl-4-methylimidazole, mix and stir for 30 minutes to form a gray electromagnetic slurry; put the slurry into a flat mold, and cure it at 80°C / 1h and 100°C / 4h to obtain a thermal conductive and wave absorbing electromagnetic functional material.

[0050] The electromagnetic parameters, attenuation coefficient, thermal conductivity and tensile strength of the heat-conducting and wave-absorbing electromagnetic functional materials prepared in Examples 1-3 and Comparative Example 1 were tested, and the test results are listed in Table 1.

[0051] Table 1 Test results of electromagnetic, thermal conductivity and strength properties of heat-conducting and wave-absorbing electromagnetic functional materials

[0052]

[0053] It can be seen from the test results in Table 1 that the preparation method of the present invention can significantly improve the electromagnetic wave attenuation performance of the functional material in a wide frequency band, improve the mechanical strength of the material, and also obtain a better thermal conductivity effect.

[0054] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a thermally conductive and wave-absorbing electromagnetic functional material, characterized in that: The following steps are involved: 1) DMSO, DMF and acetone were mixed evenly, and then BNNS powder was added and subjected to ultrasonic stirring to obtain BNNS slurry; 2) mixing the BNNS slurry with cellulose nanofibers and PVDF powder, and subjecting the mixture to ultrasonic stirring to obtain a composite spinning solution; 3) adding the composite spinning solution into a syringe and installing it in a micro-metering pump to continuously deposit BNNS / PVDF nanofibers on a carbon fiber fabric substrate to obtain a single-layer BNNS / PVDF / carbon fiber composite felt; 4) The surface of the single-layer BNNS / PVDF / carbon fiber composite felt is then covered with carbon fiber fabric, and BNNS / PVDF nanofibers are spun and deposited, and a multilayer BNNS / PVDF / carbon fiber composite felt is obtained after repeated several times; 5) heat treating the multilayer BNNS / PVDF / carbon fiber composite felt to obtain a BNNS / carbon fiber composite felt; 6) Weigh spherical carbonyl iron powder, epoxy resin, propylene oxide butyl ether, and 2-ethyl-4-methylimidazole, stir evenly, and obtain carbonyl iron powder / epoxy resin electromagnetic slurry after vacuum degassing; 7) Slowly pour the carbonyl iron powder / epoxy resin electromagnetic slurry onto the surface of the BNNS / carbon fiber composite felt, repeatedly vacuumize to make the slurry completely infiltrate into the fibrous structure, and solidify and shape to obtain a thermal conductive and wave absorbing electromagnetic functional material.

2. The preparation method according to claim 1, characterized in that In step 1), the volume ratio of DMSO, DMF and acetone is (10-15):(10-20):(5-10); if the volumes of DMSO, DMF and acetone are 10-15 mL, 10-20 mL and 5-10 mL respectively, the mass of the added BNNS powder is 0.5-1.2 g, and the BNNS powder is weighed according to the current volume-mass relationship; the specifications of the BNNS powder are: particle size 0.8-3 μm, flake diameter ratio 50-80; ultrasonic stirring is performed for 20-30 min.

3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of cellulose nanofibers to PVDF powder is (0.05-0.1):(5-12), the content of cellulose nanofibers is 0.15%-0.17%, and the content of PVDF powder is 16%-20%; ultrasonic stirring is performed for 1-1.5 hours.

4. The preparation method according to claim 1, characterized in that: In step 3), 20-35 mL of the composite spinning solution is weighed and added to the syringe. The continuous deposition conditions on the carbon fiber fabric substrate are: voltage 12-15 kV, propulsion rate 0.5-1.5 mL / h, spinning distance 10-14 cm, receiving roller speed 250-400 r / min, spinning temperature 20-25 ° C, humidity 40%-60%, and single spinning time 45-60 min.

5. The preparation method according to claim 1, characterized in that: The spinning deposition conditions in step 4) are: voltage 12-15 kV, propulsion rate 0.5-1.5 mL / h, spinning distance 10-14 cm, receiving roller speed 250-400 r / min, and repeated deposition 10-15 times.

6. The preparation method according to claim 1, characterized in that: In steps 3) and 4), the thickness of the carbon fiber fabric is 0.15 mm, and the diameter of the single fiber is 5-8 μm.

7. The preparation method according to claim 1, characterized in that: The heat treatment conditions in step 5) are: treatment at 650-800° C. for 20-40 min; the heat treatment atmosphere is a nitrogen or argon atmosphere.

8. The preparation method according to claim 1, characterized in that: In step 6), the mass ratio of spherical carbonyl iron powder, epoxy resin, propylene oxide butyl ether, and 2-ethyl-4-methylimidazole is (30-55):(35-55):(7-10):(3-5); the particle size of the spherical carbonyl iron powder is 2-3 μm, and the viscosity of the epoxy resin is 2000-2500 cps; stirring is performed for 30-40 minutes.

9. The preparation method according to claim 1, characterized in that: Step 7) Repeat the vacuuming for 6-10 times, and the vacuum-assisted single time lasts for 20-35 seconds; the curing molding conditions are: first curing at 80° C. for 1 hour, and then curing at 100° C. for 4 hours.

10. A heat-conducting and wave-absorbing electromagnetic functional material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Polyvinylidene fluoride matrix wave-absorbing magnetic composite fiber membrane and method thereof

    CN122728024A